Guava, orange and passion fruit by-products: Characterization and its impacts on kinetics of acidification and properties of probiotic fermented products - Casarotti, Sabrina N. [UNESP]; Borgonovi, Tais F. [UNESP]; Batista, Carolina L.F.M. [UNESP]; Penna, Ana Lúcia B. [UNESP] (Elsevier, 2018)
This study aimed at characterizing guava, orange and passion fruit by-products and investigating the effect of adding these fruit by-products to probiotic fermented goat milk and cereal-based fermented products. Fruit by-products showed total fiber content, phenolic compounds and antioxidant activity varying from, respectively, 58.20–89.80%, 253.14–420.89 mg GAE/100 g, and 11.38–17.37 μmol TE/g. Most carotenoids were represented by β-carotene, which ranged from 7.91 to 56.07 μg/g. The presence of fruit by-products did not affect the fermentation time of fermented oat beverage and fermented goat milk; however, a significant increase (ranging from 0.28 to 0.91 h) in fermentation time of fermented rice beverages was observed after the addition of by-products. Fruit by-products also resulted in an increase in acidification throughout storage; however, they did not affect the counts of probiotic bacteria. A decrease in probiotic survival during in vitro gastrointestinal simulation was observed in all treatments. Nonetheless, the presence of orange and passion fruit by-products enhanced the resistance of the probiotics to simulated gastrointestinal conditions and resulted in population 2 log CFU/mL higher than the control treatment. Fruit by-products can be considered relevant sources of bioactive compounds useful in raising the functional attributes of probiotic fermented products.
Keywords: Bioactive compounds; Fermented cereal-based beverage; Fermented goat milk; Functional food